2017
DOI: 10.4274/tjh.2015.0332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endocrine Late Complications in Childhood Acute Lymphoblastic Leukemia Survivors: A Report of a Single-Center Experience and Review of the Literature

Abstract: Objective:Improvement in long-term survival in patients with acute lymphoblastic leukemia (ALL) in childhood has led to the need for monitorization of treatment-related morbidity and mortality. In the current study, we aimed to evaluate endocrine side effects of treatment in ALL survivors who were in remission for at least 2 years.Materials and Methods:Sixty patients diagnosed with ALL, who were in remission for at least 2 years, were cross-sectionally evaluated for long-term endocrine complications.Results:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
3
6
0
1
Order By: Relevance
“…Based on the BMI/A measures, Nakhaei-Moghadam et al [16] found a prevalence of 29.2% overweight and 16.7% obesity, and no association between patients' weight gain and type of treatment, gender and age. According to other studies the prevalence of obesity after antineoplastic treatment of ALL in childhood varies from 16% to 56% approximately, and may be related to cranial radiation, treatment with corticosteroids, physical inactivity and increased calories intake [8,21]. Our study found a higher patients' eutrophy prevalence in M3, corroborating the data from other investigations, where the patients who survived leukemias were eutrophic utilizing the same parameters as BMI/A [17].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Based on the BMI/A measures, Nakhaei-Moghadam et al [16] found a prevalence of 29.2% overweight and 16.7% obesity, and no association between patients' weight gain and type of treatment, gender and age. According to other studies the prevalence of obesity after antineoplastic treatment of ALL in childhood varies from 16% to 56% approximately, and may be related to cranial radiation, treatment with corticosteroids, physical inactivity and increased calories intake [8,21]. Our study found a higher patients' eutrophy prevalence in M3, corroborating the data from other investigations, where the patients who survived leukemias were eutrophic utilizing the same parameters as BMI/A [17].…”
Section: Discussionsupporting
confidence: 90%
“…Our study found a higher patients' eutrophy prevalence in M3, corroborating the data from other investigations, where the patients who survived leukemias were eutrophic utilizing the same parameters as BMI/A [17]. Different results were obtained in a case-control study where the survivors of ALL in childhood were at greater risk for overweight or obesity during follow up compared to the Control Group; a significant difference in the mean weight and BMI was found, both of them being greater in the ALL survivors [21].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In recent years due to the increase in the intensity, type and dose of chemotherapy, monoclonal antibodies, large doses of immunosuppressants and targeted therapy and application of broad-spectrum antibiotics, some fungal infections have increased in newly diagnosed or relapsed leukemia patients and the incidence of oral mucosa destruction in patients has reached 40 % to 80 % [11] . Therefore, it is of great significance to find suitable methods for the protection and treatment of oral internal environment of leukemia patients after chemotherapy.…”
Section: Ineffectivementioning
confidence: 99%